Case of successful treatment of a patient suffering from diverticulitis of sigmoid intestine with perforation, bacterial and fungal sepsis, severe Thrombocytopenia and Leukopenia as complication of Covid-19 - Martyniuk , Nikita; Byk , Pavlo (The Ukrainian Scientific Medical Youth Journal, 2023)
described here is a case of successful treatment of a patient, previously ill with Covid-19, suffering from diverticular disease of sigmoid intestine with perforation that was later complicated by peritonitis, bacterial sepsis and candidal sepsis. Due to the conservative therapy in the preoperational and postoperative period and frequent usage of non-steroid anti-inflammatory drug Metamizole, patient has developed a severe case of Leukopenia and Thrombocytopenia which were partially refractory towards glucocorticoids. In lieu of lack of patient’s capability to afford treatment with recombinant human growth factors drugs, an alternative non-standard method of treatment was utilized. It included usage of Vitamin B12 + Folic Acid and other types of therapy, which allowed us to normalize leukocyte and thrombocyte levels.